The 2019 Universiti Teknologi MARA, Malaysia Staff Survey: Determining the Level and Predictors of Quality of Life - Nazali, Mohd Izwan Mat; Razali, Salmi; Ariaratnam, Suthahar; Ahmad, Yuhaniz; Nawawi, Hapizah (Frontiers in Psychiatry, 2021)
Experiencing good quality of life (QOL) among university staff is extremely crucial to ensure academic excellence, however there is limited data on the factors that contribute to QOL among university staff. This study aims to determine the level and the predictors for good QOL among university staff. The consented participants were selected using stratified sampling method. Participants who had fulfilled the selection criteria were provided with socio-demographic, medical illness, job factor and family background questionnaires. QOL and psychological well-being (depression, anxiety, and stress) were assessed using the World Health Organization Quality of Life Brief Version (WHOQOL-BREF) and Depression, Anxiety and Stress Scale (DASS-21) questionnaires, respectively. A total of 278 staff (Mean ± SD age: 38.84 ± 7.85 years, 44.2% males, 82.7% married) had participated in this study. This study found that participants had low QOL in the domains of physical health [P-QOL] (11.2%), psychological health [PSY-QOL] (9.7%), social relationships [SR-QOL] (19.1%) and environment [E-QOL] (14.4%). The predictors of P-QOL were depression, medical illness and number of dependent while PSY-QOL were work promotion, depression, medical illness and number of dependent. Additionally, the predictors of SR-QOL were campus location, depression, and work promotion whilst E-QOL were age, level of education, depression, work promotion and medical illness. Depression significantly affected all domains of QOL. Younger participants without medical illness and those with tertiary level of education had increased odds of having good QOL. Participants having dependent without work promotion and employed in the sub-urban area had decreased odds of having good QOL. Relevant authority should be identified and then assist staff with difficulties to ensure they benefited from having a good QOL.